1994
DOI: 10.1002/1097-0142(19940501)73:9<2426::aid-cncr2820730928>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of cytokines and soluble cytokine receptors in various T-cell malignancies

Abstract: Background. Cytokines, interleukin (IL)‐4, IL‐6, interferon‐gamma (IFN‐γ), tumor necrosis factor‐alpha (TNF‐α), soluble CD23 (sCD23), and soluble IL‐2 receptors (sIL‐2R) are mediators of inflammation and immune response. Alterations in immune status of patients with various cancers may result in release of cytokines in circulation. The authors measured the circulating levels of IL‐4, IL‐6, IFN‐γ TNF‐α, sCD23, and sIL‐2R from patients with T‐cell chronic lymphocytic leukemia (T‐CLL), T‐cell acute lymphoblastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
3
19
0
1
Order By: Relevance
“…Although in CML there has been one report of elevated IL-1 levels in advanced stages, 14 we did not find any such correlation of IL-1 levels with the progression of the disease. Serum TNF-levels were found to be within the 10 , and increased secretion of TNF-has been demonstrated in bone marrow cultures from CML-CP patients, 11 we did not find significantly elevated levels of TNF-in any of the cases. Serum IL-6 levels in CML-CP and CML-BC were significantly raised compared with normal controls (p=0·0026 for CML-CP and p=0·0011 for CML-BC).…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Although in CML there has been one report of elevated IL-1 levels in advanced stages, 14 we did not find any such correlation of IL-1 levels with the progression of the disease. Serum TNF-levels were found to be within the 10 , and increased secretion of TNF-has been demonstrated in bone marrow cultures from CML-CP patients, 11 we did not find significantly elevated levels of TNF-in any of the cases. Serum IL-6 levels in CML-CP and CML-BC were significantly raised compared with normal controls (p=0·0026 for CML-CP and p=0·0011 for CML-BC).…”
Section: Discussionsupporting
confidence: 47%
“…The role of these primarily monocyte-derived cytokines in CML has not been fully investigated. Some studies have indicated that elevated TNF-levels in serum are linked to poor response to interferon-(IFN-) therapy 10 , and elevated secretion of TNF-has been demonstrated in bone marrow cultures from CML-CP patients. 11 The ability of these proinflammatory cytokines to affect secretion of various colony-stimulating factors, and to act as cofactors in proliferation of stem cells, makes them an important factor in the bone marrow failure state of chronic myeloid leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…The ANT are deactivated by conjugation with sulfate or glucuronide or after demethylation of the methoxy group at ring position 4 of DOX or DAUNO. CH DOX-induced myocardial disfunction could be due to free radical formation [13], alterations of adrenergic function [14], lipid peroxidation [15], alterations in sarcolemmal CA 2+ transport [16], release of tumor necrosis factor-α and of interleukin-2 [17] and liberation of cytokine from tumor [18]. Although a close examination of the list indicates that DOXinduced injury may be multifactorial and complex, one mechanism common to most of these suggestions is the increased oxidative stress [19].…”
Section: Mechanisms Of Drug Action and Cardiotoxicitymentioning
confidence: 99%
“…Nevertheless, the exact pathogenic role of this cytokine in human cancer cachexia remains unclear. Data concerning circulating levels of TNF in cancer patients are often controversial or inconsistent [16–30]. In some studies, TNF circulating levels in cachectic patients were undetectable or, when detectable, did not correlate with the severity of weight loss [16–30].…”
Section: Introductionmentioning
confidence: 99%
“…Data concerning circulating levels of TNF in cancer patients are often controversial or inconsistent [16–30]. In some studies, TNF circulating levels in cachectic patients were undetectable or, when detectable, did not correlate with the severity of weight loss [16–30]. To explain such conflicting results it has been suggested that the analytical methods used to measure TNF serum levels were not sensitive enough, that the mechanism of action of TNF could be paracrine and, finally, that TNF secretion could be intermittent or sporadic rather than continuous [6,10] and that TNF might rapidly complex with soluble receptors [31].…”
Section: Introductionmentioning
confidence: 99%